Improved Compressed Sensing Matrixes for Insulator Leakage Current Data Compressing - Zhai Xueming; You Xiaobo; Dewen Wang (Institute of Advanced Engineering and Science, 2014)
Insulator fault may lead to the accident of power network，thus the on-line monitoring of insulator is very significant. Low rates wireless network is used for data transmission of leakage current. Determination of the measurement matrix is the significant step for realizing the compressed sensing theory. This article comes up with new sparse matrices which can be used as compressed sensing matrices to make data compression and reconstruction of leakage current with the compressed sensing. This theory can achieve pretty good results. And then this article performs that the reconstitution effect is almost the same using the measurement matrix of Toeplitz matrix, circulant matrix or sparse matrix, as using a classical measurement matrix. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.1419